Integrative computational analysis of Marburg virus protein mutations: structural and functional implications of Glycoprotein variants and natural inhibitor screening - Aktas, Emre; Ozturk, Sema; Tarhan, Bilgesu (TAYLOR & FRANCIS INC, 2026)
Marburg virus is a highly virulent filovirus responsible for severe hemorrhagic fever outbreaks with high mortality rates. This study aimed to (1) investigate the structural and functional consequences of mutations in major MARV proteins-particularly Glycoprotein (GP)-and (2) evaluate the antiviral potential of selected plant-derived compounds using computational approaches. Comparative sequence analysis identified recurrent amino acid substitutions in GP, with mutations such as P278L and D364Y predicted to induce structural damage and impact host receptor binding. Molecular dynamics simulations revealed that these mutations disrupted GP stability, altered solvent accessibility, and reduced hydrogen bonding with TYRO3 and MER receptors, potentially facilitating immune evasion and viral adaptability. Disorder prediction analysis further indicated high flexibility around these sites, reinforcing their role as mutational hotspots. To explore potential antiviral strategies, a panel of five plant-derived compounds-Aesculetin, Carvacrol, Cinnamaldehyde, Eugenol, and Geranial-was computationally screened against GP and host cell receptors (AXL, TYRO3, MER). Only Aesculetin demonstrated consistent docking scores below the -5.5 kcal/mol threshold, suggesting limited but measurable binding affinity. Other compounds exhibited weaker interactions and did not meet the minimal binding energy criterion. In contrast, known EBOV/MARV inhibitors (IN-1, IN-2, IN-3) showed significantly stronger and more stable binding profiles across all targets. Protein-ligand interaction analysis revealed that natural compounds formed fewer stabilizing contacts compared to synthetic inhibitors, though Aesculetin engaged in key hydrogen bonds and weak electrostatic/pi-cation interactions with GP. Overall, the findings highlight the structural plasticity of MARV GP, the functional relevance of specific mutations, and the potential-albeit limited-of plant-derived compounds as antiviral candidates.
Keywords: Marburg virus (MARV); Glycoprotein (GP); host receptors (AXL; TYRO3; MER); natural antiviral compounds; viral protein mutations; molecular dynamics simulations; protein-ligand docking; computational drug screening; FILOVIRUS; EVASION; EBOLA; Biochemistry & Molecular Biology; Biophysics